Discerning calvarian microvascular networks by combined optoacoustic ultrasound microscopy - Héctor Estrada; Johannes Rebling; Urs Hofmann; Daniel Razansky (Photoacoustics, 2020)
Bone microvasculature plays a paramount role in bone marrow maintenance, development, and hematopoiesis. Studies of calvarian vascular patterns within living mammalian skull with the available intravital microscopy techniques are limited to small scale observations. We developed an optical-resolution optoacoustic microscopy method combined with ultrasound biomicroscopy in order to reveal and discern the intricate networks of calvarian and cerebral vasculature over large fields of view covering majority of the murine calvaria. The vasculature segmentation method is based on an angle-corrected homogeneous model of the rodent skull, generated using simultaneously acquired three-dimensional pulse-echo ultrasound images. The hybrid microscopy design along with the appropriate skull segmentation method enable high throughput studies of a living bone while facilitating correct anatomical interpretation of the vasculature images acquired with optical resolution optoacoustic microscopy.